(untitled) (Research, Society and Development, 2022)
Objective: map evidence of training in education for aging aimed at basic education teachers. Method: a scoping review will be conducted using nine databases: Education Resources Information Center (ERIC), AgeLine (EBSCO), PubMed, Web of Science, Scopus, Scielo, Open Gray, Open Access Theses and Dissertations and Biblioteca Digital Brasileira de Theses and Dissertations (BDTD), in Portuguese, English and Spanish, with no period restriction. The keywords of the search strategy will be aligned with the acronym PCC (Population, Concept and Context) corresponding, respectively, to: teachers of basic education, education for aging and training. The evidence selection and data extraction processes will be conducted by two independent researchers. The research inclusion criteria will be guided by the PCC, including published and unpublished evidence (gray literature), with different methodological approaches, research designs and types of publication, among them: scientific articles, theses, dissertations, book chapters, documents government policies, public policies, congress proceedings and research reports. The research results will be presented in a descriptive synthesis and demonstrated by tables and diagrams for a better understanding of the data.